(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This article presents a narrative review of selected studies that investigate the impact of digital innovation on entrepreneurship and its outcomes within diverse sociopolitical contexts. The review shows that improved innovation output and the ability to absorb innovative digital models are associated with higher economic growth rates. Technological changes explain a significant portion of entrepreneurial dynamics, while regional factors also play a key role. Internet usage has led to reduced operational costs, increased sales, and enhanced customer interaction for the majority of firms, enabling rapid market expansion and stronger supplier linkages. Digitalization fosters entrepreneurship’s expansion into new markets, creating a positive feedback loop between digital adoption and firm growth. The study further highlights that government policy and institutional support have more influence on entrepreneurship sustainability than technological readiness alone. Although most examples derive from broader national and global settings, these insights highlight similar digital innovation challenges and opportunities for micro‑enterprises in emerging economies such as Manipur, where digital platforms, e‑commerce adoption, and mobile internet penetration are becoming pivotal for inclusive economic development. Future research should empirically examine how digital entrepreneurship contributes to income growth, market reach, and sustainability among smaller and tribal enterprises in such regions.